Crystal structure and negative thermal expansion properties of solid solution Er2W3-xMoxO12 - 彭杰 刘新智 郭富丽 韩松柏 刘蕴韬 陈东风 赵新华 胡中波 (Transactions of Nonferrous Metals Society of China, 2009)
A series of solid solutions Er2W3- xMOxOl2 （0.5≤x≤2.5） were successfully synthesized by the solid state method. Their crystal structures and negative thermal expansion properties were studied by high temperature X-ray powder diffraction and the Rietveld method. All samples with rare earth tungstates and molybdates crystallize in the same orthorhombic structure with space group Inca, and show the negative thermal expansion phenomena related to transverse vibration of bridging oxygen atoms in the structure. Thermal expansion coefficients （TECs） of Er2W3-xMoxO12 were determined as -16.2 × 10^-6 K^-1 for x=0.5 and -16.5 ×10^-6 K1 for x=2,5 while -20.2 × 10^-6 K^-1 and -18.4 × 10^-6 K^-1 for unsubstituted Er2W3O12 and Er2Mo3O12 in the identical temperature range of 200-800 ℃. High temperature XRD data and bond length analysis suggest that the difference between W--O and Mo--O is responsible for the change of TECs after the element substitution in the series of solid solutions.